Development of an Integrated Web-Based Multi-User Application for Village Fund Usage Reporting Using CodeIgniter - Fitriyani; Mukhsin Nuzula; Cut Lilis Setiawati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Currently, there is an increasing need for a transparent and efficient reporting system in the management of village funds (Dana Gampong), as many fund management processes still rely on manual methods or systems that are not well-integrated. Therefore, this research focuses on the development of a multi-user web-based application for reporting the use of village funds, integrated with the CodeIgniter framework. This application aims to provide a transparent and efficient system for managing and reporting village budget allocations, expenditures, and activities at various levels, including categories, fields, villages, and subdistricts. The system is designed to allow both administrators and village operators to input and manage data, ensuring accurate and up-to-date financial reporting. The admin interface enables users to update account credentials, manage categories, fields, villages, and subdistricts, while the operator interface facilitates detailed activity reporting. Additionally, the application ensures accessibility across various devices, including personal computers, laptops, tablets, and smartphones, making it flexible and user-friendly for all stakeholders. This research also explores the importance of an integrated system in improving transparency in village governance, providing a comprehensive view of fund usage across different categories and time periods.